Research, Innovation, and Diffusion of Technology - Neelameghan, A.; Seetharama, S. (Journal of Information and Knowledge, 1972)
Technological change is a key-factor affecting the economic growth, of a country. Technological change is stimulated by the knowledge generated, by research and developmental activity. There is an appreciable time-lag between the generation of an idea by research and its incorporation into the mainstream of production of commodities and services. Based on published reports, the various factors affecting the diffusion of  technology from one country to another, from one enterprise to another enterprise, and within a firm, are mentioned. Information dissemination systems at the national, regional, and institutional levels should be so designed as to facilitate the acceleration of the process of diffusion of technology between countries, between enterprises, and within an enterprise.